The Model of Environmental Education Management in Indonesia through Extracurricular Activity - Mihardja, Tumisem T (EDUCARE, 2009)
ABSTRACT: Indonesia government realizes that the formula of an effective environment policy is based on scientific information. This research mainly discusses how to develop the model of environmental education management and how to manage it in order to be continued and applicable. In the formal education in Indonesia, extracurricular activity aims to support the understanding material where the implementing done out of the class. The type of extracurricular which has direct relationship with environment is Scout Movement. The application of environmental education model through the Scout Movement activity can enhance the conservation of forest by doing reforesting. This activity is done by applying some steps there are: introduction, collection and selection of seeds, breeding, and plantation. The Scout Movement activity, however, becomes one of the education activities which is suitable for getting experience, keeping and preventing environment, and the last doing conservation. The result also shows that the application this model which is followed by a direct action to rehabilitate the damaged area is able to broaden and develop conservation area continuously in its region around the school. KEY WORDS: the model of preservation, environmental education, extra curricular activity, and the Scout movement in Indonesia.About the Author: Dr. Tumisem T. Mihardja is a Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto); and Head of Institute for Research and Community Developement in UMP, Jalan Raya Dukuhwaluh, PO Box 202, Purwokerto 53182, Central Java, Indonesia. She can be reached at: umiump@yahoo.comHow to cite this article? Mihardja, Tumisem T. (2009). âThe Model of Environmental Education Management in Indonesia through Extracurricular Activityâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.83-92. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 10, 2009); Revised (July 20, 2009); and Published (August 17, 2009).